Studi Kualitas Perairan Budidaya Rumput Laut Di Kabupaten Sumba Timur - Karel Yesaya Mbaba; Oni Ringgu Lero; Maria G.L. Wohangara (Universitas Hamzanwadi, 2024)
Research on water quality and strategies for handling seaweed washing waste provides information about management strategies aimed at finding out the quality of water in seaweed cultivation areas as a result of inappropriate handling of seaweed washing waste as well as providing information about management strategies as a recommendation and consideration for local governments. to adopt policies to overcome pollution in the East Sumba seaweed cultivation area. The measurement results show. The measurement results show that there is contamination of the water quality meters, namely pH and salinity, namely 11 and 35 respectively, while the other parameters are still below the quality standards when compared with the Republic of Indonesia government regulation number 22 of 2021, concerning the quality of marine waters for marine biota. The high pH and salinity parameters of sea water are thought to be due to the seaweed washing process carried out by seaweed farmers in the Woba expanse, where the washing process is carried out directly at the cultivation location so that there is a possibility of seaweed washing waste entering the cultivation area. Researchers suggest carrying out initial treatment to overcome water pollution.